Mathematical modelling of an ultrasonic flowmeter primary device - WALUŚ, S. (Archives of Acoustics, 1998)
The role of the primary device of an ultrasonic flowmeter is described. The author proposed a classification of the ultrasonic flowmeter primary devices based on: 1) the principle of operation of the flowmeter sensor, 2) the method of obtaining information about the measured quantity from the flow phenomenon, 3) the kind of heads (inserted in the pipe wall and clamped-on), 4) the number of ultrasonic paths and their configurations. Mathematical models of flowmeter primary devices with a point velocity measurement are calculated (for laminar and turbulent flow). Also the model for an average velocity measurement over the surface of the ultrasonic transducer inserted in flow area is given. The next models are derived for a primary device with average velocity measurements over a single segment (most frequently in pipe diameter) or over a few segments (in the multi-path ultrasonic flowmeter primary device).